2020
DOI: 10.7759/cureus.7845
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Diabetes-related Self-management on Glycemic Control in Type II Diabetes Mellitus

Abstract: Introduction: Self-care activities are behaviors adopted in order to enhance one's health. Selfcare behaviors and activities are studied in their role to enhance glycemic control, reduce diabetes-related complications, and contribute to enhancing overall quality of life in people with diabetes. The aim of this observational study was to evaluate the impact of diabetes selfcare activities and behaviors on glycemic control in people with diabetes.Methods: This observational, cross-sectional study was conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 20 publications
3
13
0
Order By: Relevance
“…Only 9-15% of individuals with type 2 diabetes achieved optimal glycemic control [15], and poor glycemic control in diabetic individuals can lead to greater sensitivity to the effects of COVID-19. A viral infection in diabetic individuals can make treatment more difficult because of sudden fluctuations in blood sugar levels and the presence of diabetes complications [5].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Only 9-15% of individuals with type 2 diabetes achieved optimal glycemic control [15], and poor glycemic control in diabetic individuals can lead to greater sensitivity to the effects of COVID-19. A viral infection in diabetic individuals can make treatment more difficult because of sudden fluctuations in blood sugar levels and the presence of diabetes complications [5].…”
Section: Discussionmentioning
confidence: 99%
“…This form was prepared by the researchers in accordance with the literature [2,13,14,16], and consisted of questions on information concerning sociodemographic characteristics and characteristics relating to illness and COVID-19.…”
Section: Patient Identification Formmentioning
confidence: 99%
See 2 more Smart Citations
“…In our patient population, the mean total DSMQ score was 6.4, which is higher compared to the mean scores of other studied population. [38][39][40] Of note, it has been demonstrated that the association between diabetes numeracy and diabetes self-management was more pronounced among patients who used insulin. 13 Furthermore, a study showed that patients with type I diabetes were found to express higher confidence in their diabetes self-management.…”
Section: Dnt-15 Score and Diabetes Self-managementmentioning
confidence: 99%